Preparation method of PEDOT: PSS-based composite fiber with silver nanoparticles loaded on surface
By mixing silver nanowires with PEDOT:PSS solution and preparing composite fibers through wet spinning process, the problem of insufficient stability of the flexible fiber SERS substrate structure in the prior art is solved, and high sensitivity, metal-grade conductivity and versatility are achieved.
Patent Information
- Application Number
- CN202411696405.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The bonding force between the metal nanomaterials of the existing flexible fiber SERS substrates and the fibers is weak, resulting in insufficient structural stability and making it difficult to achieve high sensitivity and high stability detection.
By mixing the silver nanowire solution with PEDOT:PSS solution, a spinning liquid is formed, and composite fibers are prepared by wet spinning process. The interaction between the silver nanowire and PEDOT:PSS is used to form Ag-S chemical bonds, which enhances the structural stability and detection performance of the fibers.
It realizes PEDOT:PSS matrix composite fiber with surface-loaded silver nanoparticles and internal silver nanowires, with ultra-high SERS detection sensitivity, metal-level conductivity, excellent electrical heating performance, antibacterial and droplet resistance.
Smart Images

Figure CN119530995A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of flexible sensors, in particular to a method for preparing a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface. Background Art
[0002] In order to detect viruses, toxins and human metabolites, high-performance sensors have been widely developed, such as chemical sensors, fluorescence sensors, plasmonic sensors and surface-enhanced Raman scattering (SERS) sensors. Among them, SERS sensors have attracted widespread attention due to their unique characteristics of high sensitivity, label-free and non-destructive.
[0003] At present, there are two main types of SERS substrates: solution substrates and solid substrates (including rigid and flexible substrates). Among them, the development of solution SERS substrates and rigid SERS substrates is easily restricted by sample pretreatment, in-situ and real-time detection. Flexible film SERS substrates face challenges in wearing comfort and may even cause skin inflammation in severe cases. Flexible fiber SERS substrates have excellent breathability, can greatly enhance the human wearing experience, and have great potential for practical applications.
[0004] Usually, metal nanoparticles (gold, silver, etc.) are combined with textile fibers by impregnation, hot pressing, coating, in-situ growth, etc. to be used as fiber-based SERS sensor devices. The patent "Fiber SERS substrate enriched with plasmon hotspots and its preparation method and application" provides a method for preparing a fiber SERS substrate enriched with plasmon hotspots. The method is simple and easy, and the prepared fiber SERS substrate has high detection sensitivity. However, the binding force between the metal nanomaterial and the fiber in the fiber SERS substrate prepared by the above method is weak, and the structural stability of the fiber-based SERS substrate still needs to be improved. Therefore, there is an urgent need to develop a fiber SERS substrate with high stability and high sensitivity. Summary of the invention
[0005] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles.
[0006] The technical solution of the present invention to solve the technical problem is to provide a method for preparing a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface, characterized in that the method comprises the following steps:
[0007] (1) mixing the silver nanowire solution and the PEDOT:PSS solution uniformly to obtain a spinning solution;
[0008] Alternatively, the silver nanowire solution, the PEDOT:PSS solution and the polymer solution are uniformly mixed to obtain a spinning solution;
[0009] (2) The spinning solution is squeezed into a coagulation bath through a wet spinning process and immersed to obtain a primary composite fiber; the primary composite fiber is then dried to obtain a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface and silver nanowires inside.
[0010] Compared with the prior art, the present invention has the following beneficial effects:
[0011] (1) The present invention modifies the structure inside and on the surface of the PEDOT:PSS fiber at the same time. The fiber contains a silver nanowire structure inside and a silver nanoparticle structure on the fiber surface. The presence of silver nanoparticles on the fiber surface gives it ultra-sensitive SERS sensing capability and excellent SERS detection performance, and it can be used as a flexible SERS substrate and can be applied to high-performance flexible SERS sensors. At the same time, the fiber has a complete silver nanowire structure inside and has more charge transfer channels, which makes the fiber have extremely high conductivity. In addition, the composite fiber has high conductivity, electric heating, droplet resistance and antibacterial properties, and can be used in flexible wires, wearable electric heating, antibacterial fields, health care equipment and wearable electronic information clothing.
[0012] (2) The present invention combines wet spinning technology and drying treatment technology, and uses silver nanowires to load silver nanoparticles on the surface of PEDOT:PSS-based fibers. The formation of Ag-S chemical bonds in the fiber structure strongly connects Ag and PEDOT:PSS, and the prepared composite fibers have higher structural stability.
[0013] (3) The appearance of silver nanoparticles can be attributed to the rapid evaporation of the solvent inside the fiber during the drying process and the interaction between silver nanowires and PEDOT:PSS, which forces the silver nanowire structure on the fiber surface to transform into a silver nanoparticle structure.
[0014] (4) The composite fiber of the present invention has ultra-high SERS detection sensitivity and can achieve high-sensitivity detection of low-concentration target molecules, wherein the detection limit of rhodamine 6G is 10 -11 M, Raman enhancement factor is 1.3×10 7 .
[0015] (5) The composite fiber of the present invention has more conductive channels inside, which improves the efficiency of electron transfer and promotes the improvement of conductive performance. When the concentration of silver nanowires is 0.0667 g / ml, the conductivity of the composite fiber is 1019 S / cm, which has metal-level conductive performance.
[0016] (6) The composite fiber of the present invention can be heated to 76.5° C. in a short time (~70 s) at 18 V and maintain a stable surface temperature for a relatively long time (>1000 s), and has excellent heating reliability and safety.
[0017] (7) The composite fiber of the present invention has excellent antibacterial properties and anti-dripping properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM image of the surface of the composite fiber prepared in Example 1 of the present invention;
[0019] Figure 2 is a SEM image of a cross section of the composite fiber prepared in Example 1 of the present invention;
[0020] Figure 3 10 of the composite fiber obtained in Example 1 of the present invention -11 ~10 -9 Raman spectrum of Rhodamine 6G of M;
[0021] Figure 4 This is a SERS detection reproducibility diagram of the composite fiber prepared in Example 1 of the present invention;
[0022] Figure 5 This is a SERS detection selectivity diagram of the composite fiber prepared in Example 1 of the present invention;
[0023] Figure 6 This is a conductivity diagram of the composite fiber prepared in Example 1 of the present invention;
[0024] Figure 7 This is a bending stability diagram of the composite fiber prepared in Example 1 of the present invention;
[0025] Figure 8 This is a graph showing the electrical heating performance of the composite fiber prepared in Example 1 of the present invention at different driving voltages;
[0026] Fig. 9 This is a heating stability diagram of the composite fiber prepared in Example 1 of the present invention at a constant voltage of 18V;
[0027] Fig.10 This is a digital image of Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) cultured on the composite fiber prepared in Example 1 of the present invention;
[0028] Fig.11 This is a test diagram of the resistance to molten droplets of the composite fiber prepared in Example 1 of the present invention;
[0029] Fig.12 This is a SEM image of the PEDOT:PSS fiber prepared in Comparative Example 1 of the present invention;
[0030] Fig.13 X-ray photoelectron spectra of the composite fiber prepared in Example 1 of the present invention and the PEDOT:PSS fiber prepared in Comparative Example 1;
[0031] Fig.14 The composite fiber prepared in Example 1 of the present invention and the PEDOT:PSS fiber prepared in Comparative Example 1 are 10 -5 Raman spectrum of Rhodamine 6G (R6G) of M;
[0032] Fig.15 This is a comparison chart of the electrical conductivity of the composite fiber prepared in Example 1 of the present invention and the PEDOT:PSS fiber prepared in Comparative Example 1. DETAILED DESCRIPTION
[0033] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of the present invention.
[0034] The present invention provides a method for preparing a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface (hereinafter referred to as the method), characterized in that the method comprises the following steps:
[0035] (1) Preparation of spinning solution: mixing the silver nanowire solution and the PEDOT:PSS (poly(3,4-ethylenedioxythiophene):polystyrene sulfonic acid) solution evenly to obtain a spinning solution;
[0036] Alternatively, the silver nanowire solution, the PEDOT:PSS solution and the polymer solution are uniformly mixed to obtain a spinning solution;
[0037] Preferably, in step (1), the concentration of the silver nanowire solution is 25 to 100 mg / mL (preferably 30 to 80 mg / mL, more preferably 40 to 70 mg / mL), and the solvent is preferably deionized water; the concentration of the PEDOT:PSS solution is 30 to 80 mg / mL (preferably 45 to 60 mg / mL, more preferably 50 to 55 mg / mL), and the solvent is preferably deionized water; the volume ratio of the silver nanowire solution to the PEDOT:PSS solution is 1:1 to 2 (preferably 1:2).
[0038] Preferably, in step (1), the concentration of the polymer solution is 5 to 80 mg / mL (preferably 10 to 50 mg / mL, more preferably 15 to 30 mg / mL); the volume ratio of the silver nanowire solution, the PEDOT:PSS solution and the polymer solution is 1:1 to 2:0.3 to 0.5 (preferably 1:2:0.3).
[0039] Preferably, in step (1), the polymer is any one of PVA, PAN or PVP.
[0040] Preferably, in step (1), the length of the silver nanowire is 1 to 1000 μm and the diameter is 5 to 800 nm.
[0041] Preferably, in step (1), the process for uniform mixing is: stirring at room temperature, with a stirring speed of 300 to 800 r / min and a stirring time of 30 to 180 min.
[0042] (2) Preparation of composite fibers by wet spinning: The spinning solution is squeezed into a coagulation bath through a wet spinning process and immersed to obtain nascent composite fibers; the nascent composite fibers are then dried to obtain PEDOT:PSS-based composite fibers (referred to as composite fibers) with silver nanoparticles loaded on the surface and silver nanowires inside.
[0043] Preferably, in step (2), the wet spinning process is: the extrusion speed is 5 to 35 mL / h, and the spinning temperature is room temperature.
[0044] Preferably, in step (2), the coagulation bath is at least one of isopropanol, dimethyl sulfoxide, propanol and ethylene glycol; wherein the volume ratio of isopropanol and dimethyl sulfoxide when compounded is 1 to 4: 1. Through the coagulation bath treatment, on the one hand, the spinning solution is gelled and formed through the double diffusion process of the solvent and the non-solvent, and on the other hand, the PSS is partially removed and the PEDOT molecular chain is changed into a linear structure, which is beneficial to carrier transport, thereby promoting SERS and conductivity.
[0045] Preferably, in step (2), the soaking time is 2 to 36 hours (preferably 24 hours), and the soaking temperature is room temperature.
[0046] Preferably, in step (2), the drying temperature is 30-90°C (preferably 50-60°C), the time is 5-90 min (preferably 25-90 min, more preferably 30-60 min), and the heating rate is 1-10°C / min (preferably 5°C / min).
[0047] In the embodiment, the following detection method is adopted:
[0048] (1) SERS performance detection method: The R6G solution was drop-coated on the composite fiber, and the SERS detection sensitivity of the composite fiber to the R6G molecule was tested by Raman spectrometer;
[0049] (2) Electrical property testing method: The IV curve of the composite fiber is tested, and the electrical conductivity of the composite fiber is measured based on the changes in resistance, fiber length and cross-sectional area.
[0050] (3) Multifunctional detection methods: a. Observe the electrothermal properties of the composite fiber under different driving voltages; b. Detect the antibacterial properties of the composite fiber against Escherichia coli and Staphylococcus aureus; c. Detect the droplet resistance of the composite fiber according to the combustion method.
[0051] Embodiment 1:
[0052] (1) At room temperature, 1.4 mL of 0.0526 g / mL PEDOT:PSS solution and 0.6 mL of 0.0667 g / mL silver nanowire solution were placed in a heat-collecting constant temperature heating magnetic stirrer and stirred at a speed of 500 r / min for 60 min to mix them evenly to obtain a spinning solution;
[0053] (2) A mixture of isopropanol and dimethyl sulfoxide (volume ratio of 3:1) was used as a coagulation bath. At room temperature, the spinning solution was squeezed into the coagulation solution at a rate of 5 mL / h and immersed at room temperature for 24 h to obtain nascent composite fibers. The nascent composite fibers were then dried at 60°C for 30 min at a heating rate of 5°C / min to obtain PEDOT:PSS-based composite fibers with silver nanoparticles loaded on the surface and silver nanowires inside.
[0054] Depend on Figure 1 and Figure 2 It can be seen that the surface of the composite fiber prepared in Example 1 has a silver nanoparticle structure, and the interior of the fiber has a silver nanowire structure.
[0055] Depend on Figure 3 It can be seen that the composite fiber prepared in Example 1 can detect 10 -11 ~10 -9 M's R6G;
[0056] Depend on Figure 4 It can be seen that the composite fiber prepared in Example 1 has a good SERS detection reproducibility, and the relative standard deviation is 8.57%.
[0057] Depend on Figure 5 It can be seen that the composite fiber prepared in Example 1 has excellent SERS detection selectivity and can simultaneously detect R6G and malachite green (MG) molecules.
[0058] Depend on Figure 6 It can be seen that the electrical conductivity of the composite fiber prepared in Example 1 is 1019 S / cm.
[0059] Depend on Figure 7 It can be seen that the conductivity of the composite fiber prepared in Example 1 remains stable when bent, which also means that the composite fiber structure is stable.
[0060] Depend on Figure 8It can be seen that the composite fiber prepared in Example 1 generates different amounts of heat at different driving voltages, wherein the temperature can reach 76.5° C. within 70 seconds at 18 V.
[0061] Depend on Fig. 9 It can be seen that the composite fiber prepared in Example 1 has good temperature stability under a constant voltage of 18V.
[0062] Depend on Fig.10 It can be seen that the diameter of the antibacterial zone of the composite fiber prepared in Example 1 is above 1 mm, indicating that the composite fiber has excellent antibacterial effect.
[0063] Depend on Fig.11 It can be seen that the composite fiber prepared in Example 1 did not show any droplet phenomenon during the entire combustion process.
[0064] The results of the test showed that Example 1 had a good effect. The composite fiber used as a SERS substrate could detect R6G with a sensitivity of 10 -11 M, has a good SERS detection reproducibility with a relative standard deviation of 8.57%. In addition, the composite fiber has excellent SERS detection selectivity and can simultaneously detect R6G and MG molecules.
[0065] The composite fiber also has a metal-level electrical conductivity of 1019S / cm, and the electrical conductivity remains stable when bent. The composite fiber generates different heat under different driving voltages, where the temperature can reach 76.5°C within 70s at 18V and the temperature stability is good for a relatively long time (>1000s). The diameter of the antibacterial zone of the composite fiber against Escherichia coli and Staphylococcus aureus is more than 1mm, indicating that the composite fiber has excellent antibacterial effect. The composite fiber has the characteristic of resistant to molten droplets.
[0066] Comparative Example 1:
[0067] (1) At room temperature, 0.1052 g of PEDOT:PSS particles were added to 2 ml of deionized water, placed in a heat-collecting constant temperature heating magnetic stirrer, and stirred at a speed of 500 r / min for 30 min to obtain a spinning solution;
[0068] (2) The spinning solution was squeezed into a coagulation bath of isopropanol and dimethyl sulfoxide (volume ratio of 3:1) on a wet spinning machine at a rate of 20 ml / h. After soaking at room temperature for 24 h, the fibers were fished out and dried at 60 °C for 30 min at a heating rate of 5 °C / min to prepare PEDOT:PSS fibers.
[0069] Depend on Fig.12 It can be seen that there are slight dents on the surface of the PEDOT:PSS fiber prepared in Comparative Example 1, which is caused by the rapid evaporation of the solvent inside the fiber during the drying process.
[0070] Depend on Fig.13 It can be seen that the composite fiber prepared in Example 1 has a stable structure, which is due to the generation of strong Ag-S chemical bonds on its surface.
[0071] Depend on Fig.14 It can be seen that the PEDOT:PSS fiber prepared in Comparative Example 1 has a -1 There is an obvious R6G signal at the composite fiber, which is about 3 times lower than that of the composite fiber in Example 1.
[0072] Depend on Fig.15 It can be seen that the conductivity of the PEDOT:PSS fiber prepared in Comparative Example 1 is 239 S / cm, which is about 5 times lower than the conductivity of the composite fiber in Example 1.
[0073] After testing, the SERS performance of the PEDOT:PSS fiber prepared in Comparative Example 1 is lower than that of the composite fiber; the conductivity is only 239S / cm, which is at least 5 times lower than that of the composite fiber; the temperature is heated to 42°C within 70s at 18V, and it is resistant to molten droplets but has no obvious antibacterial effect.
[0074] Embodiment 2:
[0075] (1) At room temperature, 1.4 mL of 0.06 g / mL PEDOT:PSS solution and 0.6 mL of 0.04 g / mL silver nanowire solution were stirred at 600 r / min for 80 min to mix well to prepare the spinning solution;
[0076] (2) A mixture of isopropanol and dimethyl sulfoxide (volume ratio of 2:1) was used as a coagulation bath. At room temperature, the spinning solution was squeezed into the coagulation solution at a rate of 8 mL / h and immersed in the solution at room temperature for 20 h to obtain nascent composite fibers. The nascent composite fibers were then dried at 50°C for 40 min at a heating rate of 3°C / min to obtain PEDOT:PSS-based composite fibers with silver nanoparticles loaded on the surface and silver nanowires inside.
[0077] After testing, the effect of Example 2 is good, and the detection sensitivity of the composite fiber for R6G can reach 10 -11 M, has a good SERS detection reproducibility, with a relative standard deviation of 9.1%. In addition, the composite fiber has excellent selectivity and can simultaneously detect R6G and MG molecules. The composite fiber also has a metal-level conductivity of 938S / cm, and the conductivity remains stable when bent. The composite fiber generates different heat under different driving voltages, among which the temperature can reach 68°C within 70s at 18V and has good temperature stability. The diameter of the inhibition zone of the composite fiber against Escherichia coli and Staphylococcus aureus is more than 1mm, indicating that the composite fiber has excellent antibacterial effect. The composite fiber has a droplet-resistant characteristic.
[0078] Embodiment 3:
[0079] (1) At room temperature, 2 mL of 0.05 g / mL PEDOT:PSS solution, 1 mL of 0.06 g / mL silver nanowire solution, and 0.5 mL of 0.02 g / mL PVA aqueous solution were stirred at 600 r / min for 60 min to mix uniformly to prepare the spinning solution;
[0080] (2) A mixture of isopropanol and dimethyl sulfoxide (volume ratio of 3:1) was used as a coagulation bath. At room temperature, the spinning solution was squeezed into the coagulation solution at a rate of 15 mL / h and immersed in the solution at room temperature for 24 h to obtain nascent composite fibers. The nascent composite fibers were then dried at 60°C for 40 min at a heating rate of 5°C / min to obtain PEDOT:PSS-based composite fibers with silver nanoparticles loaded on the surface and silver nanowires inside.
[0081] After testing, the effect of Example 3 is good, and the detection sensitivity of the composite fiber for R6G can reach 10 -10 M, has a good SERS detection reproducibility, with a relative standard deviation of 9%. In addition, the composite fiber can simultaneously detect R6G and MG molecules. The composite fiber also has excellent conductivity, reaching 800S / cm, and the conductivity remains stable when bent. The composite fiber generates different heat under different driving voltages, among which the temperature can reach 56°C within 70s at 18V and has good temperature stability. The diameter of the inhibition zone of the composite fiber against Escherichia coli and Staphylococcus aureus is more than 1mm, indicating that the composite fiber has excellent antibacterial effect. The composite fiber has the characteristic of resistant to melting drops.
[0082] Embodiment 4:
[0083] (1) At room temperature, 2 mL of 0.05 g / mL PEDOT:PSS solution, 1 mL of 0.06 g / mL silver nanowire solution, and 0.3 mL of 0.03 g / mL PAN aqueous solution were stirred at 500 r / min for 80 min to mix well to prepare the spinning solution;
[0084] (2) A mixture of isopropanol and dimethyl sulfoxide (volume ratio of 3:1) was used as a coagulation bath. At room temperature, the spinning solution was squeezed into the coagulation solution at a rate of 10 mL / h and immersed in the solution at room temperature for 24 h to obtain nascent composite fibers. The nascent composite fibers were then dried at 60 °C for 30 min at a heating rate of 6 °C / min to obtain PEDOT:PSS-based composite fibers with silver nanoparticles loaded on the surface and silver nanowires inside.
[0085] After testing, the effect of Example 4 is good, and the detection sensitivity of the composite fiber for R6G can reach 10 -10M, has a good SERS detection reproducibility, with a relative standard deviation of 8.2%. In addition, the composite fiber has excellent selectivity and can detect R6G and MG molecules simultaneously. Its conductivity is about 890S / cm. The diameter of the inhibition zone of the composite fiber against Escherichia coli and Staphylococcus aureus is more than 1mm, indicating that the composite fiber has excellent antibacterial effect. The composite fiber has the characteristic of resistant to molten droplets.
[0086] Embodiment 5:
[0087] (1) At room temperature, 2 mL of 0.05 g / mL PEDOT:PSS solution, 1 mL of 0.05 g / mL silver nanowire solution, and 0.5 mL of 0.015 g / mL PVA aqueous solution were stirred at 600 r / min for 90 min to mix uniformly to prepare the spinning solution;
[0088] (2) A mixture of isopropanol and dimethyl sulfoxide (volume ratio of 3:1) was used as a coagulation bath. At room temperature, the spinning solution was squeezed into the coagulation solution at a rate of 5 mL / h and immersed at room temperature for 24 h to obtain nascent composite fibers. The nascent composite fibers were then dried at 50°C for 30 min at a heating rate of 5°C / min to obtain PEDOT:PSS-based composite fibers with silver nanoparticles loaded on the surface and silver nanowires inside.
[0089] After testing, the effect of Example 5 is good, and the detection sensitivity of the composite fiber for R6G can reach 10 -10 M, has a good SERS detection reproducibility, with a relative standard deviation of 9.5%. In addition, the composite fiber has excellent selectivity and can detect R6G and MG molecules at the same time. Its conductivity is about 620S / cm. The diameter of the inhibition zone of the composite fiber against Escherichia coli and Staphylococcus aureus is more than 1mm, indicating that the composite fiber has excellent antibacterial effect. The composite fiber has the characteristic of resistant to molten droplets.
[0090] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for preparing a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface, characterized in that: The method comprises the following steps: (1) mixing the silver nanowire solution and the PEDOT:PSS solution uniformly to obtain a spinning solution; Alternatively, the silver nanowire solution, the PEDOT:PSS solution and the polymer solution are uniformly mixed to obtain a spinning solution; (2) The spinning solution is squeezed into a coagulation bath through a wet spinning process and immersed to obtain a primary composite fiber; the primary composite fiber is then dried to obtain a PEDOT:PSS-based composite fiber with silver nanoparticles loaded on the surface and silver nanowires inside.
2. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (1), the concentration of the silver nanowire solution is 25-100 mg / mL; the concentration of the PEDOT:PSS solution is 30-80 mg / mL; and the volume ratio of the silver nanowire solution to the PEDOT:PSS solution is 1:1-2.
3. The method for preparing the PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 2, characterized in that: In step (1), the concentration of the polymer solution is 5-80 mg / mL; the volume ratio of the silver nanowire solution, the PEDOT:PSS solution and the polymer solution is 1:1-2:0.3-0.
5.
4. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (1), the polymer is any one of PVA, PAN or PVP.
5. The method for preparing the PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (1), the length of the silver nanowire is 1 to 1000 μm and the diameter is 5 to 800 nm.
6. The method for preparing the PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (1), the process for uniform mixing is: stirring at room temperature, with a stirring speed of 300 to 800 r / min and a stirring time of 30 to 180 min.
7. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (2), the wet spinning process is: the extrusion speed is 5 to 35 mL / h, and the spinning temperature is room temperature.
8. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (2), the coagulation bath is at least one of isopropanol, dimethyl sulfoxide, propanol and ethylene glycol; wherein the volume ratio of isopropanol and dimethyl sulfoxide when compounded is 1 to 4:
1.
9. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (2), the soaking time is 2 to 36 hours, and the soaking temperature is room temperature.
10. The method for preparing a PEDOT:PSS-based composite fiber with surface-loaded silver nanoparticles according to claim 1, characterized in that: In step (2), the drying temperature is 30 to 90° C., the drying time is 5 to 90 min, and the heating rate is 1 to 10° C. / min.
Citation Information
Patent Citations
Flexible piezoresistive stress sensor and preparation method thereof
CN110228789A
Method for preparing flexible transparent electrode based on PEDOT:PSS and silver nanowires
CN110310763A
Organic / inorganic composite thermoelectric fiber and preparation and application thereof
CN111446355A
An artificial intelligence model for classifying liver lesions using a liver ultrasound image, a method for constructing the model, and a method for classifying a liver lesion using the artificial intelligence model
KR1020240027204A
Continuous wet-spinning process for the fabrication of pedot:PSS fibers with high electrical conductivity, thermal conductivity and young's modulus
US20200299863A1
Cited By
Conductive ink based on PEDOT: PSS and carboxylated carbon nanotubes
CN120118563A
Conductive ink based on PEDOT:PSS and carboxylated carbon nanotubes
CN120118563B
Preparation method of wearable organic semiconductor fiber SERS (Surface Enhanced Raman Scattering) sensor for analyzing glucose and uric acid in sweat
CN120231151A
A wearable organic semiconductor fiber SERS sensor for glucose and uric acid analysis in sweat
CN120231151B
Reinforced composite yarn for array spinning and spinning method
CN121110239A